UTILIZATION OF A PICO HYDRO POWER PLANT AT AL-IKHLAS ISLAMIC BOARDING SCHOOL IN MALANG REGENCY - Hidayat, Mohammad Noor; Ronilaya, Ferdian; Heryanto Eryk, Irwan; Wibowo, Sapto; Asrori, Asrori; Saputra, Masramdhani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Al-Ikhlas Yatim Dhuafa Islamic Boarding School is ± 12.6 km from Malang City. If you look at it geographically, the location of this community service program is located at coordinates 7°58'27.0"S 112°48'14.8"E. To support activities in this tourist area, electrical energy is really needed, especially for lighting facilities and charging electronic equipment. This Community Service Program will be implemented between April and November 2022 with activities in the form of building a pico hydro power plant in the Al-Ikhlas Yatim Dhuafa Islamic Boarding School area, Singosari District, Malang Regency. In carrying out this community service program, there is one activity partner, namely the Al-Ikhlas Yatim Dhuafa Islamic Boarding School with a total of 6 personnel. The results of this community service program are the installation and operation of a pico hydro power plant with a capacity of 1000 watts. This pico hydro power plant can meet electricity needs in the Islamic boarding school area with a total power of around 450 watts. In order for the pico hydro power plant to operate according to its capacity, it is necessary that the operation and maintenance of the system equipment be carried out correctly and on a schedule. For this reason, the transfer of knowledge and skills to work partners, namely the management of the Al-Ikhlas Yatim Dhuafa Islamic Boarding School, has been carried out.